PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE BAMBOO DANCING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA KELAS X KULINER DI SMK NEGERI 3 PAYAKUMBUH - Suci Rahmawati; Supriadi; Firdaus Annas; Liza Efriyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes of students in computer science, which have not reached the learning completeness level. Various problems arise from ineffective learning processes. To overcome this, it is necessary to apply learning strategies that can improve student learning outcomes. One strategy that is considered appropriate is the Bamboo Dancing cooperative learning model, as it encourages students to work together, exchange information, and solve problems related to the learning material. Based on the above issues, the research question in this study is how much influence does the Bamboo Dancing cooperative learning model have on student learning outcomes in the subject of Informatics for Grade X Culinary students at SMK Negeri 3 Payakumbuh. This type of research is quantitative research using an experimental method, employing a Non-Equivalent Control Group Design. Based on the analysis of student learning outcome test data, a t-value of 3.128 was obtained with a degree of freedom (df) = 70 and a significance level of 0.05, resulting in a significance (2-tailed) = 0.0003 (<0.005). Therefore, H0 is rejected and H1 is accepted. This shows that the Bamboo Dancing cooperative learning model has a significant effect on student learning outcomes in Informatics. The magnitude of the effect of applying this learning model based on the coefficient of determination test is 0.674 or 67.4%, which means that the use of the Bamboo Dancing cooperative learning model has a positive effect on improving student learning outcomes in Informatics for Grade X Culinary students at SMK Negeri 3 Payakumbuh.